Indirect fiber-reinforced composite resin bonded bridges : an up to 9–year retrospective clinical study - Kekki, Elina (My University, 2019)
Objective: The aim of this retrospective clinical study was to evaluate the survival and the occurrence of technical and biological complications of indirect FRC RBB (fiber-reinforced composite resin-bonded) bridges made in the student clinic of Turku University, Finland, between January 2009 and May 2015. Materials and methods: Fifty-eight FRC RBBs made for fifty-two patients were retrieved from the patient records. After screening, 48 RBBs which were fabricated in four dental laboratories, were selected for follow-up investigation. Restorations design, number of units and abutment teeth varied. The mean age of patients was 62.1 years. Twenty-seven patients were interviewed and examined with 31 FRC RBBs still in use at the time of examination. Restorations were investigated according to modified USPHS criteria with periodontal tissue health evaluated using BOP % and VPI scores. Results: The cumulative survival rate of FRC RBB restorations after 3.3 to 8.8 years (average 5.25 years) in clinical use was 62.5 % %. Out of forty-eight restorations, 18 (37.5%) were lost according to information retrieved from patient records and follow-up examinations. Debonding was the most common cause of failure (n=10) followed by fractures (n=4) and secondary caries in abutment teeth (n=4). Repairable complications occurred additionally in 11 cases, resulting in a complication rate of 20.8%. Increasing the number of RBB units and abutment teeth showed a trend towards higher failure rates. Higher survival was found for posterior (83%) than anterior (50%) restorations. Best survival rate, 75.0 %, was found for 3-unit posterior restorations. Choice of dental laboratory had a significant effect on survival. Bleeding on probing was present in 42.4 % of abutment teeth and 40.3 % of control teeth. More plaque was detected on abutment teeth (VPI score 2.15) than on control teeth (VPI score 0.85). Conclusions: FRC RBBs fabricated in laboratories with experience showed higher survival rates of 83 %. Overall survival rates were moderate (62.5 %) in this retrospective investigation with a mean observation time of 5.25 years. Choice of laboratory, location, length of the restoration and number of abutment teeth affected survival. Best prognosis was found in posterior three-unit RBBs (75.0 %). With right indications and proper design and manufacturing, indirect FRC RBBs are a practical semi-permanent treatment option in replacing missing teeth.
Keywords: fiber-reinforced composite, fixed dental prosthesis, resin bonded bridges, FRC RBB, clinical study